EFFECT OF NPK FERTILIZER DOSE AND POC CONCENTRATION GAMAL LEAVES ON GROWTH AND YIELD OF HIJAU NUT PLANT (Phaseolus radiatus) - Teguh Narimah; Endah Budi Irawati; Alif Waluyo (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2021)
The research aims to find out the influence of NPK fertilizer dose and poc concentration of gamal leaves the best to increase the growth and yield of green beans. The method used is Complete Group Random Design with 9 treatments plus 1 control and 3 replays. The first factor is the dose of NPK fertilizer (N) with N1 200 kg/ha, N2 250 kg/ha, N3 300 kg/ha and the second factor is the concentration of liquid organic fertilizer (P) with P1 20%, P2 30%, P3 40% plus control without NPK fertilizer and POC gamal leaves. The data was analyzed using diversity analysis (Anova) at a rate of 5%. To find out there is a real difference between the control and the treatment using Orthgonal Contras test at the level of 5% and when there is a noticeable difference between the treatment is carried out Duncan’s Multiple Range Test (DMRT) at the level of 5%. The results showed there was an interaction between the dose of NPK fertilizer and the concentration of POC gamal leaves at the high parameters of plants (15 and 30 HST), the number of productive branches, flowering age, number of plant pods and the number of seeds per pod (third harvest) and seed weight (harvest 1 and 2). Npk fertilizer dose 250 kg / ha gives the best results on all parameters. The concentration of 30% POC gamal leaves gives the best results on all parameters.